2017
DOI: 10.1002/rnj.233
|View full text |Cite
|
Sign up to set email alerts
|

Community Physician-Guided Long-Term Domiciliary Oxygen Therapy Combined With Conventional Therapy in Stage IV COPD Patients

Abstract: Rehabilitation nurses can be instrumental in helping patients with stage IV COPD learn principles of LTDOT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Overall, it remains unclear whether LTOT reduces healthcare use. One retrospective study [ 33 ] found fewer hospitalisations over 3 years in the LTOT group compared with conventional therapy (mean difference: −1.17, 95% CI −1.73–−0.59), whereas an observational study could not confirm that finding [ 34 ].…”
Section: Copd and Hypoxaemic Respiratory Failurementioning
confidence: 99%
“…Overall, it remains unclear whether LTOT reduces healthcare use. One retrospective study [ 33 ] found fewer hospitalisations over 3 years in the LTOT group compared with conventional therapy (mean difference: −1.17, 95% CI −1.73–−0.59), whereas an observational study could not confirm that finding [ 34 ].…”
Section: Copd and Hypoxaemic Respiratory Failurementioning
confidence: 99%